Laporan kunjungan kerja Komisi IV DPR-RI pada masa reses persidangan I tahun sidang 1990-1991 (Dewan Perwakilan Rakyat, Republik Indonesia, 1990)
Forestry, transmigration, and agricultural affairs; report of a visit of the 4th Commission of Parliament.